Extraction, Structural Characterization, and Anti-Hepatocellular Carcinoma Activity of Polysaccharides From Panax ginseng Meyer - Jia, Hui; Zhao, Bin; Zhang, Fangfang; Santhanam, Ramesh Kumar; Wang, Xinying; Lu, Jincai (Frontiers in Oncology, 2021)
Polysaccharides are the main active ingredients of ginseng. To extract the most effective polysaccharides against hepatocellular carcinoma (HCC), we isolated and characterized the polysaccharides from the mountain cultivated ginseng (MCG) and compared their composition and cytotoxic effect with cultivated ginseng (CG) polysaccharide against HepG2 cell lines for the first time. MCG polysaccharides and CG polysaccharides were fractionated into two fractions such as MTPS-1, MTPS-2 and CTPS-1, CTPS-2 by salting out, respectively. Compared to CG, MCG possessed appreciable cytotoxic effect against HepG2 cells among that MTPS-1 possess fortified effect. Then, MTPS-1 was selected for further isolation process and seven acidic polysaccharides (MCGP-1 MCGP-7) were obtained using ethanol precipitation, ion-exchange and gel permeation chromatography techniques. Structural characteristics of the polysaccharides (MCGP-1 MCGP-7) were done by adapting methylation/GC-MS and NMR analysis. Overall, MCGP-3 polysaccharide was found to possess significant cytotoxic effect against HepG2 cells with the IC50 value.